Olhinhos de Nuvens: Infância e Solidão na prosa de Cecília Meireles - Gomes, Jennifer Pereira (2014)
This work aims to observe the figurations of childhood - in that case, girls - and loneliness in prose of memoir nature of Cecília Meireles. We seek to bring us closer to a portion of the work in Ceciliana prose that, compared to other books, are less covered by literary criticism: Olhinhos de gato (autobiographical novel) and Giroflê, giroflá (short stories) . From the in-depth reading of selected works, following the comparative method, we understand (and appreciate) figurations of childhood, focusing on female children's characters: they are children who have a slope facing the poetic, the reverie (identified as characteristic of imagination child), immersed in solitude, with great proximity to death, beyond the intimate experience of transcendence. Watching the stylistic development of the text of the author (imagery, vocabulary choice, sound, theme, etc.) we believe we can still make an approximation that the corpus poetry and other prose of the author, perform a thematic perspective. From the "poetics of the senses" proposed by Gaston Bachelard in The poetic of reverie we’ll realize how is the experience of the world performed by the girls of the corpus of works, observing the oniric spaces where they are and will position us from the exploitation of space, compared to daydreaming, miniaturization, and the transcendence whose principle infinite.